The Effect of Financial Knowledge, Financial Self-Efficacy, Lifestyle, and Financial Attitude on Household Financial Management Behavior among Housewives in Kubu Raya Regency - Dessi Aprilyani; Heni Safitri; Dedi Hariyanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the effect of financial knowledge, financial self-efficacy, lifestyle, and financial attitude on household financial management behavior among housewives in Kubu Raya Regency. This study uses a causal associative method. The population in this study consists of all housewives residing in Kubu Raya Regency, with a sample of 150 respondents determined using purposive sampling. Based on the multiple linear regression analysis, the regression equation is obtained as follows: Y = 1.128 + 0.205X₁ + 0.238X₂ + 0.201X₃ + 0.135X₄. The correlation coefficient result shows a value of 0.708, indicating a strong relationship between financial knowledge, financial self-efficacy, lifestyle, and financial attitude on financial management behavior. The coefficient of determination shows a value of 0.501, meaning that financial management behavior is influenced by financial knowledge, financial self-efficacy, lifestyle, and financial attitude by 50.1%. The simultaneous test results indicate that financial knowledge, financial self-efficacy, lifestyle, and financial attitude jointly have a positive and significant effect on household financial management behavior among housewives in Kubu Raya Regency. The partial test results show that financial knowledge, financial self-efficacy, lifestyle, and financial attitude each have a positive and significant effect on financial management behavior.